2008
DOI: 10.1016/j.envres.2008.07.014
|View full text |Cite
|
Sign up to set email alerts
|

Urinary metabolite concentrations of organophosphorous pesticides, bisphenol A, and phthalates among pregnant women in Rotterdam, the Netherlands: The Generation R study

Abstract: Concern about potential health impacts of low level exposures to organophosphorus (OP) pesticides, bisphenol A (BPA), and phthalates among the general population is increasing. We measured levels of six dialkyl phosphate (DAP) metabolites of OP pesticides, a chlorpyrifos-specific metabolite (3,5,6-trichloro-2-pyridinol, TCPy), BPA, and fourteen phthalate metabolites in urine samples of 100 pregnant women from the Generation R study, the Netherlands. The unadjusted and creatinineadjusted concentrations were rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
122
11
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 286 publications
(154 citation statements)
references
References 45 publications
19
122
11
2
Order By: Relevance
“…First, in a study examining spot urine samples collected from 100 pregnant Dutch women, Ye et al (2008b) detected total BPA in 82% of samples, with a median concentration of 1.2 ng/mL urine, similar to the levels of BPA detected in other populations, including U.S. reference populations (Calafat et al 2005). An even larger study examined urine from 404 American women in their third trimester of pregnancy.…”
Section: Exposure Assessment From Urinary Measures Of Bpamentioning
confidence: 99%
“…First, in a study examining spot urine samples collected from 100 pregnant Dutch women, Ye et al (2008b) detected total BPA in 82% of samples, with a median concentration of 1.2 ng/mL urine, similar to the levels of BPA detected in other populations, including U.S. reference populations (Calafat et al 2005). An even larger study examined urine from 404 American women in their third trimester of pregnancy.…”
Section: Exposure Assessment From Urinary Measures Of Bpamentioning
confidence: 99%
“…These urine samples are used for measurement of several environmental exposures, and metabolites. Urine samples have been used for measurement of Chlamydia, and pesticides, bisphenol A, and phthalates levels [155,156].…”
Section: Biological Samplesmentioning
confidence: 99%
“…Bisphenol A (BPA, 4,4'-isopropylidenediphenol) is widely used to manufacture numerous plastic products including food can linings and clear plastic bottles and several population studies have reported a high degree of human exposure [4,42]. There is controversial data about the safety of these products.…”
Section: Introductionmentioning
confidence: 99%